Bad News: Analysis of the Quality of Information on Influenza Prevention Returned by Google in English and Italian - Maki, Ali; Evans, Roger; Ghezzi, Pietro (Frontiers in Immunology, 2015)
Information available to the public influences the approach of the population towards vaccination against influenza compared with other preventative approaches. In this study we have analyzed the first 200 websites returned by searching Google on two topics (prevention of influenza and influenza vaccine), in English and Italian. For all the four searches above, websites were classified according to their typology (government, commercial, professional, portals etc.) and for their trustworthiness as defined by the Journal of the American Medical Association (JAMA) score which assesses whether they provide some basic elements of information quality (IQ): authorship, currency, disclosure and references. The type of information described was also assessed to add another dimension of IQ. Websites on influenza prevention were classified according to the type of preventative approach mentioned (vaccine, lifestyle, hygiene, complementary medicine etc.), whether the approaches were in agreement with evidence based medicine (EBM) or not. Websites on influenza vaccination were classified as pro- or anti-vaccine, or neutral). The great majority of websites described EBM approaches to influenza prevention and had a pro-vaccine orientation. Government websites mainly pointed at EBM preventative approaches and had a pro-vaccine orientation, while there was a higher proportion of commercial websites among those which promote non-EBM approaches. Although the JAMA score was lower in commercial websites, it did not correlate with the preventative approaches suggested or the orientation toward vaccines. For each of the four search engine result pages (SERP), only one website displayed the health-of-the-net (HON) seal. In the SERP on vaccines, journalistic websites were the most abundant category and ranked higher than average in both languages. Analysis using natural language processing showed that journalistic websites were mostly reporting news about two specific topics (different in the two languages). While the ranking by Google favours EBM approaches and, in English, does not promote commercial websites, in both languages it gives a great advantage to news. Thus, the type of news published during the influenza season probably has a key importance in orienting the public opinion due to its high visibility. This raises important questions on the relationships between health IQ, trustworthiness and newsworthiness.